THE FIXED MEANS: AN ACCOUNTING CONCEPT OR A FISCAL ONE? - Rotila, Aristita (Studies and Scientific Researches. Economics Edition, 2014)
Starting from the analysis of the accounting regulations applied to the economic operators, in their evolution after 1989, the specific accounting regulations for certain fields of activity and for certain categories of entities and starting from the fiscal rules and some paper works, we want to clarify in this study some conceptual issues referring to the fixed means, the tangible fixed assets components, of impacting financial information, respectively, on taxation. Is the concept of “fixed means” an accounting one or a fiscal one? We try to answer to this question and also to formulate an opinion on whether it is longer justified to use this concept in the accounting vocabulary and hence in the production of information presented in financial statements or in the fiscal vocabulary and implicitly in the work done to produce information provided in the fiscal reports.